2014
DOI: 10.2204/iodp.proc.342.102.2014
|View full text |Cite
|
Sign up to set email alerts
|

Methods

Abstract: X-ray diffraction analyses Bulk sample XRD analyses were performed using a Bruker D-4 Endeavor X-ray diffractometer with a Vantec detector using Ni-filtered CuKα radiation. Instrument settings were Voltage = 40 kV. Current = 40 mA. Goniometer scan = 2°-70°2θ (air-dried samples). Step size = 0.01°2θ. Scan speed = 1.2°2θ/min. Count time = 0.5 s. Biostratigraphy Preliminary age assignments were based on biostratigraphic analyses of calcareous nannofossils, planktonic foraminifers, and radiolarians. Paleodepth int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 82 publications
(125 reference statements)
0
20
0
Order By: Relevance
“…S. delphix has a reported longevity of 100 k.y. (see Table T1 in the "Methods" chapter [Norris et al, 2014a]) and is found through a 27 m interval at Site U1405 (Samples 342-U1405A-19H-6, 46 cm, to 22H-4, 110 cm;175.66-201.80 mbsf). The Miocene/Oligocene boundary interval also contains at least one carbonate-rich layer with common to abundant Braarudosphaera (Fig.…”
Section: Calcareous Nannofossilsmentioning
confidence: 99%
See 2 more Smart Citations
“…S. delphix has a reported longevity of 100 k.y. (see Table T1 in the "Methods" chapter [Norris et al, 2014a]) and is found through a 27 m interval at Site U1405 (Samples 342-U1405A-19H-6, 46 cm, to 22H-4, 110 cm;175.66-201.80 mbsf). The Miocene/Oligocene boundary interval also contains at least one carbonate-rich layer with common to abundant Braarudosphaera (Fig.…”
Section: Calcareous Nannofossilsmentioning
confidence: 99%
“…The raw WRMS data for Hole U1405A were trimmed at section ends to remove edge effects; obviously spurious data points were also removed. We multiplied the WRMS data, which are in instrument units, by a factor of 0.577 × 10 -5 to convert to approximate SI volume susceptibilities (see "Paleomagnetism" in the "Methods" chapter [Norris et al, 2014a]). WRMS and DSMS data agree very well after this conversion, and we attribute small absolute differences to the fact that the conversion factor applied to the WRMS data is not constant downhole because of changes in core diameter and density; only discrete samples provide calibrated susceptibility values in SI units.…”
Section: Magnetic Susceptibility and Anisotropy Of Magnetic Susceptibmentioning
confidence: 99%
See 1 more Smart Citation
“…Downhole variation in raw whole-round magnetic susceptibility (WRMS) and discrete sample magnetic susceptibility (DSMS) for Hole U1404A are shown in Figure F19. We multiplied the WRMS data, which are in instrument units, by a factor of 0.577 × 10 -5 to convert to approximate SI volume susceptibilities (see "Paleomagnetism" in the "Methods" chapter [Norris et al, 2014b]). WRMS and DSMS data agree very well after this conversion, and we attribute small absolute differences to the fact that the conversion factor applied to the WRMS data is not constant downhole because of changes in core diameter and density; only discrete samples provide calibrated susceptibility values in SI units.…”
Section: Magnetic Susceptibility and Anisotropy Of Magnetic Susceptibmentioning
confidence: 99%
“…Rew = reworked. See "Biostratigraphy" in the "Methods" chapter (Norris et al, 2014b) for preservation and abundance definitions. Table T8.…”
Section: Site U1404mentioning
confidence: 99%